VARIASI FENOTIP DAN GENOTIP EBONI (Diospyros celebica Bakh) PADA HUTAN ALAM DAN HUTAN TANAMAN DI SULAWESI TENGAH DAN SULAWESI BARAT - Wahyuningsih Wahyuningsih; Muslimin Muslimin; Yusran Yusran (ForestSains, 2017)
The aim of this research are to know phenotype and genotype diversity between population of ebony on the forest in Sulawesi specially from Central Sulawesi and West Sulawesi. The study was conducted from January to April 2014, extraction of  DNA has been done in laboratory of  Biotechnology, faculty of Mathematics and Natural Science, Tadulako University and DNA analysis in Kyoto Perfectural University, Japan. PCR-RAPD technique was employed in this study with 4 RAPD primers. Sample from 9 population in natural forest and plant forest in Central Sulawesi and West Sulawesi and all leaf sample taken show different. There were 2 primary that resulting the best amplifying quality in genotype diversity analysis that was TCH05 and AS9870. There is unique bands on DNA fragment from Lende area, has band size 2500-3000bp while from ebony individu sample from other area locus cannot be found. Based on dendogram analysis on distance matrix revealed the 10 genotypes were grouped into two main groups. The first group population from Lende. The second group was further divided into two sub group (2A and 2B). Subgroup 2A consisted of Diospyros kaki. Subgroup 2B included population from Ako, Tibo, Bale, Tompe, Maleali, and Kasimbar.